Adsorptive Behavior of Tartaric Acid Treated Holarrhena antidysenterica and Citrullus colocynthis Biowastes for Decolourization of Congo Red Dye from Aqueous Solutions - Sumaira Basharat; Rabia Rehman; Sara Basharat (Journal of Chemistry)
The aim of the present work is to eradicate Congo red (CR) dye from aqueous solutions since the dye compounds are harmful to human life and the environment leading to detrimental results. For this purpose, Holarrhena antidysenterica (HA) and Citrullus colocynthis (CC) adsorbents were used for the adsorptive removal of Congo red dye from wastewaters. The unmodified adsorbents (U-HA and U-CC) were chemically modified using tartaric acid (TA). Morphological structures were examined by FTIR and SEM. Batch adsorption studies were tested at a variety of pH, time exposure, temperatures, and adsorbent dosages. Thermodynamic parameters such as Gibbs free energy (∆G°), enthalpy (∆H°), entropy changes (∆S°), and energy of activation (Ea) were also calculated. The results revealed that tartaric acid-Citrullus colocynthis (TA-CC) gave optimum conditions of time of contact (35 min), temperature conditions (40°C), pH (3), and dosage of adsorbent (1.6 g) for maximum dye removal. Tartaric acid-Holarrhena antidysenterica (TA-HA) gave equilibrium time of contact (30 min), temperature (40°C), and pH optimum (2) along with a 1.6 g dosage of adsorbent. Mechanistic understanding of adsorption isotherm provided that the Langmuir model was followed by raw and modified adsorbents. Maximum adsorption capacities Qmax attained were 60.61 (mg g-1), 128.21 (mg g-1), 87.71 (mg g-1), and 131.57 (mg g-1), respectively, for U-HA, TA-HA, U-CC, and TA-CC. The results of kinetic modeling displayed a high value of R2 (0.99) along with minimal error (RMSE) for dye removal showing that the pseudo-second-order kinetic model has acceptable accuracy. Fourier transform infrared proposed the electrostatic, pi-pi interactions, and hydrogen bonding as dominant adsorption mechanisms at acidic pH, respectively. Rate-determining steps comprise both surface and intraparticle diffusions. Thermodynamics indicated that the dye adsorption of CR is spontaneous, exothermic, and favorable in nature. These agricultural wastes due to specific points such as low cost, availability, and high removal rates of adsorption are highly competent for the expulsion of anionic dye like CR from wastewaters.